Systemic and renal oxidative stress in the pathogenesis of hypertension: modulation of long-term control of arterial blood pressure by resveratrol - Hamza, Shereen M.; Dyck, Jason R. B. (Frontiers in Physiology, 2014)
Hypertension affects over 25% of the global population and is associated with grave and often fatal complications that affect many organ systems. Although great advancements have been made in the clinical assessment and treatment of hypertension, the cause of hypertension in over 90% of these patients are unknown, which hampers the development of targeted and more effective treatment. The etiology of hypertension involves multiple pathological processes and organ systems, however one unifying feature of all of these contributing factors is oxidative stress. Once the body’s natural anti-oxidant defense mechanisms are overwhelmed, reactive oxygen species (ROS) begin to accumulate in the tissues. ROS play important roles in normal regulation of many physiological processes, however in excess they are detrimental and cause widespread cell and tissue damage as well as derangements in many physiological processes. Thus, control of oxidative stress has become an attractive target for pharmacotherapy to prevent and manage hypertension. Resveratrol (trans-3,5,4'-Trihydroxystilbene) is a naturally occurring polyphenol which has anti-oxidant effects in vivo. Many studies have shown anti-hypertensive effects of resveratrol in different pre-clinical models of hypertension, via a multitude of mechanisms that include its function as an anti-oxidant. However, results have been mixed and may be due to the heavy emphasis on peripheral vasodilator effects of resveratrol with virtually no investigation of its potential renal effects. This is troubling in the arena of hypertension, where it is accepted that the kidney plays an essential role in the long term regulation of arterial pressure and a vital role in the development and maintenance of chronic hypertension. Thus the focus of this review is to discuss the potential of resveratrol as an anti-hypertensive treatment via amelioration of oxidative stress within the framework of physiological principles of blood pressure control.